The Printing Press as an Agent of Change / Communications and Cultural Transformations in Early-Modern Europe Volumew I and II - Eisenstein Elisabeth L (Cambridge University Press, 1979)
An extensive survey of the recent literature on the three intellectual and social movements of the period 1400-1700. Preface, Introduction to an Elusive Transformation, The Unacknowledged Revolution, Defining the Initial Shift; Some Features of Print Culture, Classical and Christian Traditions Reoriented; Renaissance and Reformation Reapraised, A Classical Revival Reoriented; The Two Phases of the Renaissance, The Scriptural Tradition Recast: Resetting the Stage for the Reformation, The Book of Nature Transformed, Introduction; Problems of Periodization, Technical Literature Goes to Press: Some New Trends in Scientific Writing and Research, Resetting the Stage for the Copernican Revolution, Sponsorship and Censorship of Scientific Publication, Scripture and Nature Transformed, Index.